Altered movement strategy during functional movement after an ACL injury, despite ACL reconstruction - Stenroth, Lauri; Bartholdy, Cecilie; Schwarz Larsen, Jonas; Sørensen, Mads Skipper; Smale, Kenneth B.; Flaxman, Teresa E.; Benoit, Daniel L.; Krogsgaard, Michael R.; Alkjær, Tine (Frontiers in Sports and Active Living, 2022)
Knee joint functional deficits are common after anterior cruciate ligament (ACL) injury, but different assessment methods of joint function seem to provide contradicting information complicating recovery monitoring. We previously reported improved perceived knee function and functional performance (forward lunge ground contact time) in patients with an ACL injury from pre to 10 months post ACL reconstruction without improvement in knee-specific biomechanics. To further investigate this discrepancy, we additionally analyzed knee extensor and flexor muscle strength, and movement quality in the forward lunge (subjective and objective evaluations) and performed a full lower limb biomechanical analysis of the forward lunge movement. We included 12 patients with an ACL injury (tested before and after ACL reconstructive surgery) and 15 healthy controls from the previous study to the current investigation. Outcome measures were obtained pre and ~11 months post ACL reconstruction for the patients and at a single time point for the controls. Objective movement quality in the patients with an ACL injury showed an improvement from their pre reconstruction surgery visit to the post reconstruction visit but this was not observable in the subjective evaluation. Knee extensor muscle strength declined after the ACL reconstruction by 29% (p = 0.002) and both knee extensors (p < 0.001) and flexors (p = 0.027) were weaker in the patients post ACL reconstruction compared to healthy controls. ACL injured patients had an altered movement strategy in the forward lunge with reduced knee extensors contribution and increased hip extensor contribution compared to the controls both before and after the reconstruction. The altered movement strategy was associated with knee extensor muscle strength. This explorative study with a limited sample size found that clinicians should be aware that significant functional deficits in the knee extensor muscles, both in isolated muscle strength testing and during a functional movement, may be present although patients perceive an improvement in their knee function and present good functional performance without obvious movement quality issues.